Efect of pH and temperature on the fermentation and flocculation capacity of strainns of Saccharomyces stored at mycotheca- URM. II. (Boletín Micológico, 1995)
The combined effect of pH medium (10% aqueous solution of molasses) and incubation temperature in the expression of fermentation capacity and flocculation of 12 strains of Saccharomyces stored at the Micoteca-URM were studied. Of these, 11 strains belong to S. cerevisiae and1 to S. kluyveri. They were tested at pH 4,5 and 5 and incubation temperatures of 28°e ± 1ºC (room temperature), 25°C and 37°C. All the strains fermented in media with both pH rates and in the 3 temperature of incubation. However period of fermentation and flocculation varied according to different pH and temperature.